After Sale Service to Imported Goods in Realizing Law Enforcement of Consumer Protection - Frederik, Wulanmas A. P. G (Indonesian Journal of International Law, 2021)
The prominent issue in globalization era is the emergence of great attention to the issues of the law enforcement of consumer protection and the distribution of the incoming imported goods freely to Indonesia. The impact of open economic embraced by Indonesia causes the swift flow of goods and service into Indonesian territory. The effect of Indonesia in international economy is insignificant, but in contrary, the effect of International economy to Indonesian economy is highly significant. Consequently, the insignificant Indonesian effect on international economy causes Indonesia is having difficulty to compete in international trade. Therefore, Consumer Protection Act becomes public needs for protection and promotion of human interest as the consequence of the selling and purchase transaction of imported goods. The After Sale Service for imported goods is one of aspects covered by consumer protection as sellers have obligations to deliver the goods and is responsible for losses incurred by consumers due to use of the goods. This article would examine how law enforcement of consumer protection can be against after-sales service issues.